Prognostic factors in 264 adults with invasive Scedosporium spp. and Lomentospora prolificans infection reported in the literature and FungiScope®. (2nd January 2019) - Seidel, Danila; Meißner, Arne; Lackner, Michaela; Piepenbrock, Ellen; Salmanton-García, Jon; Stecher, Melanie; Mellinghoff, Sibylle; Hamprecht, Axel; Durán Graeff, Luisa; Köhler, Philipp; Cheng, Matthew P.; Denis, Julie; et al.
Abstract: Invasive Scedosporium spp. and Lomentospora prolificans infections are an emerging threat in immunocompromised and occasionally in healthy hosts. Scedosporium spp. is intrinsically resistant to most, L. prolificans to all the antifungal drugs currently approved, raising concerns about appropriate treatment decisions. High mortality rates of up to 90% underline the need for comprehensive diagnostic workup and even more for new, effective antifungal drugs to improve patient outcome. For a comprehensive analysis, we identified cases of severe Scedosporium spp. and L. prolificans infections from the literature diagnosed in 2000 or later and the FungiScope ® registry. For 208 Scedosporium spp. infections solid organ transplantation ( n  = 58, 27.9%) and for 56  L. prolificans infection underlying malignancy ( n  = 28, 50.0%) were the most prevalent risk factors. L. prolificans infections frequently presented as fungemia ( n  = 26, 46.4% versus n  = 12, 5.8% for Scedosporium spp.). Malignancy, fungemia, CNS and lung involvement predicted worse outcome for scedosporiosis and lomentosporiosis. Patients treated with voriconazole had a better overall outcome in both groups compared to treatment with amphotericin B formulations. This review discusses the epidemiology, prognostic factors, pathogen susceptibility to approved and investigational antifungals, and treatment strategies of severe infections caused by Scedosporium spp. and L. prolificans .